The Use of Mononucleosome Immunoprecipitation for Analysis of Combinatorial Histone Post-translational Modifications and Purification of Nucleosome-Interacting Proteins - Khan, Kashif Aziz; Ng, Marlee K.; Cheung, Peter (Frontiers in Cell and Developmental Biology, 2020)
The nucleosome is the principal structural unit of chromatin. Although many studies focus on individual histone post-translational modifications (PTMs) in isolation, it is important to recognize that multiple histone PTMs can function together or cross-regulate one another within the nucleosome context. In addition, different modifications or histone-binding surfaces can synergize to stabilize the binding of nuclear factors to nucleosomes. To facilitate these types of studies, we present here a step-by-step protocol for isolating high yields of mononucleosomes for biochemical analyses. Furthermore, we discuss differences and variations of the basic protocol used in different publications and characterize the relative abundance of selected histone PTMs and chromatin-binding proteins in the different chromatin fractions obtained by this method.Word count: 6175